The Political Thought of the Civil War - Stoner, James R.; Merrill, Thomas W. (Thomas Westneat), 1974-; Levine, Alan, 1961- (Book collections on Project MUSE., 2018)
"The Civil War continues to speak so powerfully to us because it was a constitutional moment in which the meaning and soundness of the regime was put in doubt. In The Political Thought of the Civil War, leading scholars of American political thought take a "deliberative" approach to the war, meaning they engage with the words and deeds of the most thoughtful political actors of the time with respect to questions about the regime, specifically regarding the place of slavery, the tension between morality and constitutionalism, and the potential of the principles of the American regime to build a multiracial, multicultural society. By starting with the actors, and the difficult choices they made in response to specific problems, the contributors to this volume are able to explore the theoretical principles at play in the controversy within their historical context. The essays are divided into three sections that examine, respectively, the practical dilemma to which the war was the response, the difficult decisions Americans made in the face of a collapsing regime, and the consequences of those choices"--